2021
DOI: 10.1051/0004-6361/202038654
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal shear instabilities in rotating stellar radiation zones

Abstract: Context. Stellar interiors are the seat of efficient transport of angular momentum all along their evolution. In this context, understanding the dependence of the turbulent transport triggered by the instabilities of the vertical and horizontal shears of the differential rotation in stellar radiation zones as a function of their rotation, stratification, and thermal diffusivity is mandatory. Indeed, it constitutes one of the cornerstones of the rotational transport and mixing theory, which is implemented in st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…In the case where the dynamics is dominated by the horizontal shear, assuming τ ∼ 1/S θ further leads to a horizontal viscosity coefficient that is proportional to the horizontal shear rate, which is consistent with the viscosity coefficient derived by Park et al (2021). We note that, in contrast, Garaud (2001) found that the horizontal shear instability can lead to an anti-diffusive horizontal transport of angular momentum.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the case where the dynamics is dominated by the horizontal shear, assuming τ ∼ 1/S θ further leads to a horizontal viscosity coefficient that is proportional to the horizontal shear rate, which is consistent with the viscosity coefficient derived by Park et al (2021). We note that, in contrast, Garaud (2001) found that the horizontal shear instability can lead to an anti-diffusive horizontal transport of angular momentum.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, the comparison with the Rayleigh-Taylor instability stands only in the special case where 2Ω + sin θS r > 0 and cos S θ < 0. Thus, the criterion |S θ | < 2 could be linked to some other hydrodynamical instability instead, such as the inertial or the inflectional instability studied by Park et al (2020Park et al ( , 2021. The form of the expression of u θ u ϕ in Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guenel et al (2016a,b) did observe instabilities with conical differential rotation, but only for sufficiently low viscosities, whereas our study shows little dependence on the friction and rather highlights possible over-transmission for non-linear flows. Lastly, we underline that a temporal analysis on the growth rate of perturbations should be undertaken to unravel instabilities, which has not been performed in this paper but has been in other separate papers (Park et al 2020(Park et al , 2021.…”
Section: Discussionmentioning
confidence: 99%